Facilitators and obstacles to the use of a cognitive orthosis for meal preparation within the homes of adults with a moderate to severe traumatic brain injury: Informal caregivers and health-care professionals' perspectives. Issue 3 (4th May 2022) - Gagnon-Roy, M.; Bier, N.; Couture, M.; Giroux, S.; Pigot, H.; Zarshenas, S.; Bottari, C.
ABSTRACT: A cognitive orthosis named COOK was developed and implemented to facilitate meal preparation for adults with severe traumatic brain injury (TBI) living in an alternative housing unit. This study aimed to explore facilitators and barriers to the potential use and implementation of COOK in a new context (i.e., within the homes of people living with a TBI in the community). For this purpose, 20 stakeholders (e.g., health-care professionals, clinical coordinators, informal caregivers of individuals with TBI) were interviewed. Participants identified various potential benefits of this technology (e.g., improving independence and confidence of people with TBI) and facilitators (e.g., clinical and technical supports, helpful functionalities) that could facilitate the use and implementation of COOK within a home environment. However, numerous questions remained unanswered regarding the logistics surrounding the implementation of such technology. Thus, further studies and modifications are required to facilitate future implementation of this technology among individuals living in their own homes.